Exploring the Influence of Audiovisual Tools on Youth and their Social Adaptation in Elementary Education - Al Hussaini, Muzamil Hussain; Arcelus-Ulibarrena, Juana Maria (The Indonesian Institute of Science and Technology Research, 2023)
Technology has been a part of our lives for decades. We have become so used to it that it has become second nature to us, particularly when it comes to audiovisual aids. Audiovisual aids such as videos, movies and even video games have significantly impacted young people's lives and how they perceive the world around them. But what does this mean for their social adjustment? How are audiovisual aids impacting how today's youngsters interact with their peers, family members, and strangers? The study's objective has been discussed, and the hypothesis testifies to these objectives. The population of this research work is students admitted to different public schools, and samples were taken from different tehsils via proportionate random sampling techniques. Data collected by questionnaire and instrument checked by pilot testing, validity by various experts working in educational sectors and via Cronbach Alpha and other statistical analysis reliability process has been completed. After data analysis, some discussion & results on findings and conclusion and implication of this study. This study explored how audiovisual aids impact youngsters' social adjustment and how we use these tools to help foster healthier relationships.